Molecular systematics of New Zealand skinks of the genus Cyclodina : a thesis presented in partial fulfillment of the requirements for the degree of Master of Science in Genetics at Massey University, New Zealand - Slack, Kerryn Elizabeth (Massey University, 1996)
The taxonomic status, relationships and possible origin(s) of eight skinks from the genus Cyclodina were investigated using molecular systematics - one from each of the six recognised and two proposed New Zealand species. DNA sequence data from the mitochondrial 12S ribosomal RNA gene was obtained using the polymerase chain reaction (PCR) and a thermocycling-based sequencing procedure. Phylogenetic analysis was carried out using spectral analysis, which utilizes new and sophisticated algorithms, and the maximum parsimony, minimum evolution and maximum likelihood options of PAUP* Version 4.0, a new test version of PAUP. New Zealand members of the skink genus Leiolopisma and three overseas skinks were also included in analyses. A single resolved tree was not produced, which may indicate that the New Zealand Cyclodina diverged rapidly. The eight Cyclodina taxa form genetically distinct lineages, supporting the separate taxonomic status of each of the recognised and proposed species. The suggestion that the C. aenea population from the Poor Knights Islands is a separate species is well supported, the two C. aenea taxa being separated by and/or pairing with other taxa in most trees. However, the possibility of subspecific status cannot be excluded for C. oliveri from the Mokohinau Islands (the second proposed new species). While the eight Cyclodina taxa form a closely related group, L. fallai pairs with C. alani and L. zelandicum with the Poor Knights C. aenea in many or all of the phylogenies. L. moco and the Mauritian skink L. telfairi also appear to have links with Cyclodina. The level of spectral analysis and bootstrap support is low for most of these relationships; nevertheless a monophyletic origin for Cyclodina with regards to the New Zealand Leiolopisma is not supported under the present taxonomic classification. Longer sequences from additional genes and a larger, more diverse set of skinks are required (in conjunction with other molecular, morphological and ecological information) before the exact relationships of these taxa and the origin(s) and divergence times of the New Zealand Cyclodina can be accurately determined. However, the results of this study do suggest that Cyclodina is older than previously thought, possibly even Gondwanan in origin.
Keywords: New Zealand Skinks; Classification